TERRA INCOGNITO SURREALISME YOGYAKARTA - Dr. M. Dwi Marianto, M.F.A. (Ars: Jurnal Seni Rupa dan Desain, 2007)
Surrealism, which was coined in the First Manifesto o f Surrealism by Andre Breton in 1924,indeed begun and was centred in Paris, before spreading nut to a number o f countries beyond F.urop?,including the Pacific region. Interestingly, in the Surrealist international map published in 1929, Francewas not there, and it was as i f the USA never existed, whereas it was the Pacific Regioti which was regardedas the centre o f the world. The Parisian Surrealist highly appreciated art from the region. As a mutter offad,there were really artists in a number o f countries, including Indonesia, who were well-accepted andappropriated Surrealism according to their respected culture. In Yogyakarta, surrealists' works o f artemerged phenomenally in the 1970s and have been continuously produced until now. RegardingIndonesian surrealism, M. Dioi Marianto suggests that surrealism exists in any culture and society. TheParisian culture did not come to Yogyakarta directly but through reproductions o f Surrealists’ w o rkprinted in Modem Art books. Images o f surrealist works were then seen and adopted by many artists asuxiys o f producing surrealistic works o f art. In this resjyect it is more appropriate to regard the ParisianSurrealism as having triggered surrealist virtual potentials or tendencies that hud indeed been embedded inthe culture and sub-cultures streaming through Yogyakarta as a state o f mind.Keyu>ords: Surrealism, Parisian Surrealist, state o f mind